Losartan improves intestinal mucositis induced by 5-fluorouracil in mice - Maisie Mitchele Barbosa Oliveira; Aurigena Antunes de Araújo; Susana Barbosa Ribeiro; Polyana Crislayne Moreira de Sales Mota; Vitória Barros Marques; Conceição da Silva Martins Rebouças; Jozi Godoy Figueiredo; Patrícia Batista Barra; Gerly Anne de Castro Brito; Renata Ferreira de Carvalho Leitão; Gerlane Coelho Bernardo Guerra; Caroline Addison Carvalho Xavier de Medeiros (Scientific Reports, 2021)
Abstract Intestinal mucositis (IM) is a common side effect of 5-fluorouracil (5-FU)-based chemotherapy, which negatively impacts therapeutic outcomes and delays subsequent cycles of chemotherapy resulting in dose reductions and treatment discontinuation. In search of new pharmacological alternatives that minimize your symptoms, this work set out to study the effect of losartan (LOS), a receptor type I (AT1) angiotensin II antagonist, on intestinal mucositis induced by 5-FU. Intestinal mucositis was induced by a single intraperitoneal administration of 5-FU (450 mg/kg) in Swiss mice. Losartan (5, 25 or 50 mg/kg) or saline was orally administered 30 min before 5-FU and daily for 4 days. On 4th day, the animals were euthanized and segments of small intestine were collected to evaluate histopathological alterations (morphometric analysis), concentration of inflammatory cytokines, oxidative stress markers and genic expression of NF-κB p65, Fn-14 and TWEAK. Weight evaluation and changes in leukogram were also analyzed. 5-FU induced intense weight loss, leukopenia and reduction in villus height compared to saline group. Losartan (50 mg/kg) prevented 5-FU-induced inflammation by decreasing in the analyzed parameters compared to the 5-FU group. Our findings suggest that 50 mg/kg of losartan prevents the effects of 5-FU on intestinal mucosa in mice.